Comparing the Effects of Professional Method of PETTLEP-Based Imagery and Traditional Techniques of Imagery on Learning Badminton Short Service (Backhand) - Mohammad Afroozeh; Mohsen Afrooze (University of Tehran, 2010)
The aim of this research was to examine the effects of PETTLEP-based imagery compared to more traditional imagery on learning badminton short service (backhand). For this purpose, 45 male students (age 12-14 years) were non-randomly selected and divided into three groups of 15 students each (they were beginners). The groups exercised in the following way: first group performed PETTLEP-based imagery and practical training. Participants in the PETTLEP imagery group applied the physical principles of PETTLEP imagery training. They were requested to imagine performing badminton short service wearing their complete badminton competition uniform; second group performed traditional techniques of imagery and practical training. Participants in the traditional imagery group engaged in a relaxation session before imagery; third group performed practical training. In 7th, 14th, 21st and 28th session, all subjects performed French test. The obtained data were analyzed by ANOVA and Tokey tests. The results showed a significant difference between PETTLEP-based imagery and traditional technique of imagery groups in learning badminton short service technique. There was a significant difference between traditional technique of imagery group and control group in learning badminton short service technique. In retention test, there was a significant difference between PETTLEP-based imagery with traditional technique of imagery and control group in learning badminton short service technique. It is suggested that coaches and physical educators use PETTLEP when possible.